1997
DOI: 10.1590/s0100-879x1997000400013
|View full text |Cite
|
Sign up to set email alerts
|

The myth of nitric oxide in central cardiovascular control by the nucleus tractus solitarii

Abstract: Considerable evidence suggests that nitroxidergic mechanisms in the nucleus tractus solitarii (NTS) participate in cardiovascular reflex control. Much of that evidence, being based on responses to nitric oxide precursors or inhibitors of nitric oxide synthesis, has been indirect and circumstantial. We sought to directly determine cardiovascular responses to nitric oxide donors microinjected into the NTS and to determine if traditional receptor mechanisms might account for responses to certain of these donors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several investigators [57,[59][60][61][62][63][64][65][66][67][68][69][70][71] have reported data for the effects of microinjection of NO related substances into the NTS on circulation. In 1991, Lewis et al…”
Section: Nucleus Tractus Solitariusmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators [57,[59][60][61][62][63][64][65][66][67][68][69][70][71] have reported data for the effects of microinjection of NO related substances into the NTS on circulation. In 1991, Lewis et al…”
Section: Nucleus Tractus Solitariusmentioning
confidence: 99%
“…Recently, Talman [69] published a paper entitled "The myth of nitric oxide in central cardiovascular control by the nucleus tractus solitarii." He and his colleagues [67,69] found that microinjection of L-Snitrosocysteine (L-SNC) into the NTS decreased the ABP in contrast to D-S-nitrosocysteine (D-SNC), which produced minimal responses, although L-and D-SNC released identical amounts of NO.…”
Section: Nucleus Tractus Solitariusmentioning
confidence: 99%
See 1 more Smart Citation